Assessment of vehicular pollution in Kathmandu: magnetic properties and heavy metal chemistry of dust from streets and leaves - Gautam, Pitambar; Blaha, Ulrich; Appel, Erwin (Journal of Nepal Geological Society, 2012)
Road sediment (solid inorganic material accumulated on the road surface) and leaf-dust (dust deposited on leaves of short, <1 m in height, roadside rubber plants) samples collected from the roads of Kathmandu were studied for magnetism (magnetic susceptibility ?, isothermal remanence IRM, anhysteretic remanence ARM, and microscopy) and contents of heavy metals (HM: Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Zn), to judge their suitability to assess the traffic-related urban environment pollution. Bulk samples (grain diameter: <0.63 mm) of road sediment samples at 10 sites, from both major and minor roads, had ? within (0.6–3.5) × 10-6 m3/kg. Both ? and IRM showed strong inverse relationship with size fractions. Magnetite-like phase, of both geogenic and anthropogenic origin, is the dominant magnetic material. In general, the finer the grain size fraction the higher the HM content; compared to the coarse fraction, the fine fraction was enriched 1.5 times in Ni and 4 times in Pb. For a particular size fraction, however, ? had no clear relationship with HM content implying its limited use as a universal proxy of the HM enrichment in non-regulated urban roads. For bulk samples of leaf dust from 14 sites, ? had a range of (0.9–2.6) × 10-6 m3/kg, with notably lower values for those along secondary roads or largely off the road margin even in the case of major roads. Based on X-ray assisted microscopy, magnetite or magnetite-like phase having soft-coercivity, in magnetic terms, contributes to ca. 88% of saturation IRM. The magnetic susceptibility of leaf dust correlates well with the contents of urban elements (Zn, Cu, and Pb) and thus serves as a good proxy of the vehicular metallic pollution. Jour. Nep. Geol. Soc., Vol. 37, 2008, 67-76